Fourteen years clinical evaluation of leucite-reinforced ceramic inlays luted using two different adhesion strategies. (August 2022) - Taschner, Michael; Stirnweiss, Anna; Frankenberger, Roland; Kramer, Norbert; Galler, Kerstin M.; Maier, Eva
Abstract: Objectives: Aim of the present prospective study was to clinically evaluate the long-term performance of two different luting-materials for leucite-reinforced glass-ceramic inlays/onlays after 14 years. Methods: A total of 83 IPS-Empress-inlays/onlays were placed in 30 patients. Restorations were luted according to two different strategies: 43 restorations were fixed with a self-adhesive resin-cement (RelyXUnicem, RX), 40 restorations were inserted with VariolinkII-low (SV) after pretreatment with an etch-and-rinse multi-step adhesive. Recalls were performed after two weeks ( n =83), two years ( n = 82), four years ( n =74) and 14 years ( n =54). Two independent calibrated examiners evaluated all restorations using modified USPHS-criteria. Statistical analysis was performed using pairwise Mann-Whitney-U-test and Friedman-test ( p < 0.05). Results: After 14 years, 54 restorations in 22 patients were evaluated (eight patients equalling 29 inlays not available). Ten restorations had to be replaced (failure rate 12%); four (SV-group) showed bulk fractures and two (RX-group) exhibited marginal fractures at the 14-year recall. Overall, the SV-group revealed significantly better results regarding discoloration of the luting gap ( p <0.05) compared to the RX-group. No statistically significant differences were computed between SV and RX for the remaining criteria at the respective recalls (p>0.05). However, statistically significant deteriorations were detected for both luting procedures over 14 years regarding "colour match", "marginal integrity" and "tooth integrity" (p<0.05). Conclusions: The self-adhesive resin-cement RelyXUnicem showed similar clinical performance to a conventional multi-step luting-procedure after 14 years for most of the test parameters with a slightly inferior performance of RelyXUnicem regarding discoloration of the luting gap. Clinical significance: The current study presents unique in-vivo long-term data on two adhesion-strategies for indirect ceramic single-tooth restorations. Differences in performance of the two luting methods after being challenged for 14 years in the oral environment are highlighted. However, the overarching survival rate justifies the recommendation of both methods for clinical routine.